2021
DOI: 10.25176/rfmh.v21i1.3181
|View full text |Cite
|
Sign up to set email alerts
|

Preventive measures against SARS-CoV-2 in the community: What does the evidence say?

Abstract: La pandemia del COVID-19 ha tenido un gran impacto a nivel mundial y nacional. El Perú, hasta el 27 de julio, ocupa el séptimo lugar a nivel mundial con más de 400,600 casos diagnosticados y 18,816 personas fallecidas (1) . Sumado a esto, se levantó la cuarentena obligatoria impuesta a la población desde el mes de marzo (en la mayoría de las regiones). Por todo esto, se debe hacer énfasis en la importancia y eficacia de las medidas de prevención comunitarias, basada en la evidencia, que han demostrado benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…An important finding is that distance from the customer protects against cell phone contamination. Although no study has evaluated the effect of the distance between people on avoidance of cell phone contamination, several studies have shown the effectiveness of this measure in protecting against contagion by the SARS-CoV-2 virus [46,47]. Indeed, it is likely that individuals who maintain a greater distance from people for protective purposes against SARS-CoV-2, according to Peruvian government measures, are also more attentive to the hygiene of their cell phone.…”
Section: Discussionmentioning
confidence: 99%
“…An important finding is that distance from the customer protects against cell phone contamination. Although no study has evaluated the effect of the distance between people on avoidance of cell phone contamination, several studies have shown the effectiveness of this measure in protecting against contagion by the SARS-CoV-2 virus [46,47]. Indeed, it is likely that individuals who maintain a greater distance from people for protective purposes against SARS-CoV-2, according to Peruvian government measures, are also more attentive to the hygiene of their cell phone.…”
Section: Discussionmentioning
confidence: 99%